Association Between Social Networking Service Use and Body Image Among Elementary School Children in Japan - Asami Baba; Masumi Suzuki; Rikako Yoshitake; Yumiko Inose; Naomi Omi (European Journal of Investigation in Health, Psychology and Education, 2025)
The number of studies suggesting that social networking services (SNSs) use poses a risk to children’s body image continue to expand, but most studies have focused on adolescents. The study aimed to examine the associations between SNS use and body image among elementary school children in Japan. This study examined the relationship between SNSs use and body size perception and preference, body size misperception, and ideal body image among 1261 preadolescents (611 boys and 650 girls), aged 8–12 years (mean age = 9.64; SD =1.15; 52% girls), separately by sex. Using hierarchical multivariate linear regression analyses and logistic regression analyses, we examined body image factors and SNS use as the dependent and independent variables, respectively. Findings indicate that children who use SNSs do not significantly differ from nonusers regarding body dissatisfaction. However, SNS use is positively associated with body size misperception in girls. Additionally, for boys and girls, SNS use seems to increase the likelihood of admiring the body image of media figures rather than friends or classmates. Understanding how SNS use influences body image remains important for promoting healthy development in children.